PENGARUH MOTIVASI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PLN (PERSERO) DISTRIBUSI DI DENPASAR BALI - Pramadita, AA Gde Oka; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2015)
PLN in Denpasar Bali in achieving and supporting the mission of the World Class Services , requires skills ( skills), skills and exemplary work. The purpose of research to identify the variables of motivation, discipline and work environment significantly affects the performance of employees at PT PLN ( Persero ) Distribution in Denpasar Bali. Testing data using multiple linear regression. Sampling method using slovin formula, where the sample was taken as many as 137 respondents. Analysis proves variables motivation, discipline and work environment influence simultaneously and partially on the performance of employees of PT PLN ( Persero ) Distribution in Denpasar Bali. The work environment is a dominant influence on the performance of PT PLN ( Persero ) Distribution in Denpasar Bali .
Keywords: kinerja; motivasi; disiplin kerja; lingkungan kerja